ITINERARY WISATA BOYOLALI-SOLO-KLATEN - Bianca Debby; Jap Tji Beng; Wasino Wasino (Fakultas Teknologi Informasi Universitas Tarumanagara, 2018)
Making travel plan before going travelling is an important thing. With travel plan, we can easily get the whole picture for our travelling and make the trip more efficient because we don’t need to think about what place should be visited when we get there. Boyolali, Solo, and Klaten is an area in Central Java with lots of beautiful nature and historical heritage. The purpose of this system is to help people who wants to make their own travel plan (itinerary). Beside that, this system also take part in promoting places or tourist attractions in Boyolali, Solo, and Klaten.The methods used for collecting data are literature study and observation. The research method used is SDLC (System Development Lifecycle) method and the programming language used is PHP with MySQL database